Innovation in public sector organisations - Mahmoud Moussa (Taylor & Francis Group, 2018)
Public sector organisations around the globe consider the development of new ideas and innovation paramount and inevitable. This is attributable to the intense global competition and rapid technological development. Innovation is the successful implementation of ideas and processes to tackle existing problems and develop new opportunities. The in-depth literature review identified leadership behaviours, the impact of organisational climate and culture on innovation, and barriers to overcome in order to promote innovation in the public sector. A conceptual model illustrates the relationships between innovation and other critical concepts identified throughout the paper.